Tingklat Pengetahuan Anggota Pecinta Alam Dalam Mitigasi Bencana Gempabumi Di SMA Negeri 1 Kartasura Sukoharjo - NURKHOIRIAH, Dina, Dr. Kuswaji Dwi Priyono, M. Si (2015)
Research was conducted on the active members of nature lovers SMA 1 Kartasura Sukoharjo district to determine the level of knowledge about disaster mitigation earthquake. The variables used were active members' knowledge of nature lovers mitiasi against earthquake disaster. The population used are all members active nature lovers were 30 to 12 students as administrators and 18 students younger members. The analytical method used is quantitative descriptive analysis. Data collection used questionnaires and interviews. Based on research hasi and discussion of members' knowledge level research nature lovers SMA 1 Kartasura against tectonic earthquake disaster mitigation in the category "High" with a percentage of 66.67% and a score of 280. The non-structural mitigation already transactions are carried out in SMA Negeri 1 Kartasura ie, schools that have the front page class is quite extensive and wide roads for escape route in the event of earthquake. Basketball is widely owned by the school that could allow as the assembling points or evacuation in case of earthquake.